IINFLUENCE OF HEAT TREATMENTS WITH CONCENTRATED ENERGY SOURCES ON THE CAST IRONS MECHANICAL PROPERTIES (Nonconventional Technologies Review, 2017)
The cast irons and steels are alloys frequently used in industry, reason for why they favour the application of various technologies to improve the properties. Depending on the applications is searched the suitable technological process. The paper presents the results obtained by applying the heat treatment with concentrated energy sources on gray cast iron and nodular cast iron. In terms of the studied properties, the hardening (quenching) heat treatment with concentrated sources establishes the substantially improving of these, compared with conventional hardening. For the studied gray cast iron the best results are obtained for the laser hardening. In the case of nodular cast iron, throughout the laser hardening offers the best values for the studied properties. For both types of hardening with concentrated sources, the values of the obtained properties by the use cathode beam are close of those obtained with laser. By applying the hardening with the concentrated energy sources either laser or cathode beam is obtained a significant improvement of the studied properties: micro hardness, hardness and wear resistance. As in the steel case the hardening with the concentrated energy sources applied to cast iron causes the improving of the certain properties.
Keywords: cast irons; concentrated energy sources; mechanical properties